Mosaic Hemagglutinin-Based Whole Inactivated Virus Vaccines Induce Broad Protection Against Influenza B Virus Challenge in Mice - Liu, Yonghong; Strohmeier, Shirin; González-Domínguez, Irene; Tan, Jessica; Simon, Viviana; Krammer, Florian; García-Sastre, Adolfo; Palese, Peter; Sun, Weina (Frontiers in Immunology, 2021)
Influenza viruses undergo antigenic changes in the immuno-dominant hemagglutinin (HA) head domain, necessitating annual re-formulation of and re-vaccination with seasonal influenza virus vaccines for continuing protection. We previously synthesized mosaic HA (mHA) proteins of influenza B viruses which redirect the immune response towards the immuno-subdominant conserved epitopes of the HA via sequential immunization. As ~90% of current influenza virus vaccines are manufactured using the inactivated virus platform, we generated and sequentially vaccinated mice with inactivated influenza B viruses displaying either the homologous (same B HA backbones) or the heterologous (different B HA backbones) mosaic HAs. Both approaches induced long-lasting and cross-protective antibody responses showing strong antibody-dependent cellular cytotoxicity (ADCC) activity. We believe the B virus mHA vaccine candidates represent a major step towards a universal influenza B virus vaccine.